Multicomponent DNA Polymerization Motor Gels. Issue 37 (9th August 2020) - Shi, Ruohong; Fern, Joshua; Xu, Weinan; Jia, Sisi; Huang, Qi; Pahapale, Gayatri; Schulman, Rebecca; Gracias, David H.
Abstract: Hydrogels with the ability to change shape in response to biochemical stimuli are important for biosensing, smart medicine, drug delivery, and soft robotics. Here, a family of multicomponent DNA polymerization motor gels with different polymer backbones is created, including acrylamide‐ co ‐bis‐acrylamide (Am‐BIS), poly(ethylene glycol) diacrylate (PEGDA), and gelatin‐methacryloyl (GelMA) that swell extensively in response to specific DNA sequences. A common mechanism, a polymerization motor that induces swelling is driven by a cascade of DNA hairpin insertions into hydrogel crosslinks. These multicomponent hydrogels can be photopatterned into distinct shapes, have a broad range of mechanical properties, including tunable shear moduli between 297 and 3888 Pa and enhanced biocompatibility. Human cells adhere to the GelMA‐DNA gels and remain viable during ≈70% volumetric swelling of the gel scaffold induced by DNA sequences. The results demonstrate the generality of sequential DNA hairpin insertion as a mechanism for inducing shape change in multicomponent hydrogels, suggesting widespread applicability of polymerization motor gels in biomaterials science and engineering. Abstract : Photopatterned multicomponent DNA polymerization gels with tunable stiffness and biocompatibility are developed, all of which significantly swell in response to the sequential insertion of DNA hairpins. The results validate the generality of the DNA polymerization motor, which is an important mechanism for inducing extensive shape change in hydrogels of relevance to soft matter and DNA nanotechnology.